Organization of Independent Work of Students in the Context of the Development of Critical Thinking - Dilorom Sherbekovna Ulasheva (Genius Publishing Group, 2023)
The article focuses on the problem of developing students' critical thinking skills, which help them become independent learners. Analysis of research works of educators and scholars enable the authors to reveal qualities, necessary for students to enhance their critical thinking skills and become independent learners. Different points of view on the problem are given. The authors pay attention to the big role of command, team work.
Keywords: Independent learning; critical thinking; conditions; skills